Perancangan Sistem Informasi Peminjaman dan Pengembalian Barang Laboratorium di SMK Negeri 1 Solok Selatan - Ami Anggraini Samudra; Thomson Mary; Feni Susilawati (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2021)
Recording at the SMK N 1 Solok Selatan laboratory has been carried out by writing all transactions on paper or in folio notebooks. The difficulty in this recording process is in terms of data storage and retrieval. In addition, a manual filing system can cause some archival data to be lost or tucked away in one place and also cause some items to be lost, and labor officers still have difficulty managing reports of labor goods with frequent duplication of processing item data, and difficulties in updating item data. according to certain conditions. From this problem, an information system for borrowing and returning laboratory goods was designed using the Unified Modeling Language (UML) model and the Software Development Life Cycle (SDLC) method which in this model has several stages, namely the planning stage, the analysis stage, the design stage, the implementation stage, the testing phase and the maintenance stage. This information system for borrowing and returning laboratory goods is carried out by testing Blackbox testing and in accordance with this test system can facilitate the process of borrowing and returning goods between members and labor officers when borrowing and returning goods, as well as labor officers with the head of labor in the problem of borrowing reports and return of goods. Keywords: Information systems, Unified Modeling Language (UML), Software  Development Life Cycle (SDLC),Laboratorium.